Effect of cervical relining of acrylic resin copings on the accuracy of stone dies obtained using a polyether impression material - André Tomazini Gomes de Sá; César Antunes de Freitas; Fátima Cristina de Sá; Wagner José Silva Ursi; Tânia Christina Simões; Márcia Furtado Antunes de Freitas (University of São Paulo, 2008)
The purpose of this study was to evaluate the accuracy of the respective dies after polyether elastomeric procedure in the presence or absence of cervical contact of the acrylic resin shell with the cervical region, establishing a comparison to dies obtained with stock trays. This study consisted of three groups with 10 specimens each: 1) acrylic copings without cervical contact, (cn); 2) acrylic copings with cervical contact (cc); 3) perforated stock tray, (st). The accuracy of the resulting dies was verified with the aid of a master crown, precisely fit to the master steel die. ANOVA test found statistically significant differences among groups (p<0.001). Tukey's test found that the smallest discrepancy occurred in group cn, followed by cc, while the st group presented the highest difference (cc x cn: p=0.007; st x cn: p<0.001; st x cc: p<0.001).